Gambaran Personal Hygiene Pada Penjamah Makanan Di Instalasi Gizi Rumah Sakit Madani Palu - Bungawati, A; Subagyo, Indro; Sri Wahyuni , Indri (Poltekkes Kemenkes Bengkulu, 2025)
Food poisoning is a global health problem that still occurs frequently, especially in hospital settings. This study aims to describe the personal hygiene practices of food handlers in the Nutrition Installation of Madani Hospital, Palu City. The study used a descriptive method with an observational and interview approach involving all 17 food handlers. The observed variables included handwashing habits, the use of gloves, masks, head coverings, aprons, the cleanliness of clothing and nails, as well as the habit of not smoking during food processing. The results showed that all respondents had practiced regular handwashing, used head coverings and aprons, maintained clean clothing and nails, and did not smoke while working. However, only one respondent (6%) met the requirements for using plastic gloves, and two respondents (12%) had not used masks according to standards. The high level of compliance in several aspects was supported by the availability of facilities, continuous education, supervision, and a positive work culture. The conclusion of this study indicates that the implementation of personal hygiene in the Nutrition Installation of Madani Hospital is fairly good in several aspects, but deficiencies remain in the use of gloves and masks. Continuous improvements are needed through supervision, refresher training, and the provision of adequate facilities to support optimal personal hygiene practices, thereby improving the quality of food processing and food safety in the hospital.